SISTEM PENDIDIKAN PESANTREN MODERN STUDI KASUS PENDIDIKAN PESANTREN DI PONDOK PESANTREN SUMATERA THAWALIB PARABEK - Yuliani , Wulantika; Wati, Salmi; Bisdawati, Bisdawati (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Education as an effort to improve the quality of human life, both physical and spiritual, individual and social, must be based on a planned system and followed by the implementation of an appropriate and correct curriculum. This is intended to achieve the desired educational goals and is in line with current developments. Therefore, the success of the educational process is very dependent on the curriculum used, although this does not deny the importance of the role of other educational aspects.Considering that the role of the curriculum in an education system is so vital, every educational institution must be able to implement and systematize a form of curriculum that is considered capable of leading to ideal educational conditions. Conditions that describe the essence of the aim of education in forming individuals who are intellectually capable, skilled and moral and able to demonstrate their existence as an educational institution that is able to survive in every development of the times without having to give up its original identity. as an educational institution that consistently maintains old traditions.